Subcutaneous Administration of Insulin is Associated With Regional Differences in Injection Depot Variability and Kinetics in The Rat - Gradel, Anna Katrina Jógvansdóttir; Porsgaard, Trine; Lykkesfeldt, Jens; Brockhoff, Per Bruun; Seested, Torben; Refsgaard, Hanne Hoffmann Frølund (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background In humans, subcutaneous administration of insulin in the abdominal region or arm is associated with a faster absorption compared to the thigh or buttocks. We hypothesised that this is partly caused by differences in injection depot structure and kinetics and that the variability in insulin exposure differs between injection sites.Material and methods Regional effects on insulin pharmacokinetics were evaluated in a series of studies in Sprague Dawley rats dosed subcutaneously with insulin aspart in the neck or flank. Injection depots were visualised using µCT after subcutaneous dosing with insulin aspart mixed with the contrast agent iomeprol, and insulin exposure was determined between the scans by Luminescent Oxygen Channeling Immunoassay.Results Insulin absorption was significantly delayed by subcutaneous dosing in the flank compared to the neck region (p<0.01 or less). This delay was associated with smaller depots, as measured by reduced depot volume and surface area (p<0.001). Furthermore, the delayed absorption correlated with a slower depot disappearance (p<0.001). Regional differences in depot variability were not reflected by similar differences in pharmacokinetic variability.Conclusion Structure and kinetics of subcutaneous injection depots—as detected by µCT scans—predict insulin exposure and may thus contribute to the regional differences in insulin pharmacokinetics. The present methodology is applicable for visualisation of insulin injection depots in vivo. Our results did however not support a link between the variability in depot size and insulin pharmacokinetics.
Keywords: In vivo pharmacology; insulin pharmacokinetics; variability; µCT imaging